Sheep Corneal Endothelium Morphology - Evaluation with Trypan Blue and Alizarin Red - Marchionatti Pigatto, Anita; Neves Boeloni, Jankerle; Poersch Seibel, Maiara; Fernandez da Silva, Alessandra; Valim Borges de Vargas, Eduarda; Gallicchio Azevedo, Mariane; Rech Cassanego, Guilherme; De Nardin Peixoto, Gabriella; Karianne Brandenburg, Natália; Antonio Tadeu Pigatto, João (Acta Scientiae Veterinariae, 2022)
Background: The endothelium is a layer fundamental to maintaining corneal transparency. In ophthalmology, sheep eyes have been used as a model in research related to corneal transplantation. Different techniques have been used to evaluate the corneal endothelium. Concerning vital dyes, corneal endothelial cell analyses have not yet been studied in ovines. The purpose of the present study was to evaluate the morphology of endothelial cells from different regions of the cornea of sheep after staining with alizarin red and trypan blue using an optical microscope. Materials, Methods & Results: Twenty healthy eyes of 10 male sheep obtained from a licensed commercial slaughterhouse were studied. The study was approved by the Research Committee of the Faculty of Veterinary at UFRGS and followed the ethical standards of the Association for Research in Vision and Ophthalmology (ARVO). Immediately after the slaughter, the eyes were enucleated and underwent eye examination. The corneal endothelium was stained with trypan blue and alizarin red and examined and photographed using an optical microscope. The central, superior, inferior, nasal and temporal areas of the cornea were evaluated for cell morphology. Data were compared by t-tests. Differences were considered statistically significant at P < 0.05. Immediately after staining the corneal endothelium, it was possible to examine with an optical microscope, obtain images and analyse the shape of endothelial cells from all regions of the sheep cornea. Polygonal, uniform and continuous cells were observed in all samples studied. Considering all the corneas analysed, cells with 6 sides (75.11%), 5 sides (12.76%) and 4 sides (12.12%) were found. In the central region of the cornea 75.91% of cells with 6 sides, 12.6% of cells with 5 sides and 11.48% with 7 sides were found. In the superior region of the cornea 76.07% of cells with 6 sides, 13.25% with 5 sides and 10.68% with 7 sides were found. In the lower region were found 74.72% of cells with 6 sides, 13% with 5 sides and 12.27% with 7 sides. In the temporal region, 74.14% were 6-sided cells, 11.42% had 5 sides, and 14.43% had 7 sides. Furthermore, in the nasal region, 74.72% of the cells had 6 sides, 13.54% had 5 sides, and 11.73% had 7 sides. No significant differences were found between cell morphology in all corneal regions evaluated. In addition, no significant difference was found when comparing the right eye with the left eye. Discussion: Different methods are used for the analysis of corneal endothelium. For ex vivo research optical microscopy after endothelial staining is an alternative low-cost technique that allows the analysis of all regions of the cornea. Quantitative analyses must characterise the endothelial parameters of the different species. The analysis of the morphology of corneal endothelium with an optic microscope after staining with alizarin red has been described as an effective, rapid and cost-efficient method, since this dye blends with the borated cells, allowing identification. In the present study, using optical microscopy and coloration with alizarin red it was possible to explore and obtain images of the ovine endothelium of all regions of the cornea. In the current study, the endothelium had a predominance of cells will 6 sides in all regions studied. This study allowed us to obtain images of the endothelium as well as quantitative data on the morphology of the different regions of the sheep cornea. This study demonstrated that morphology did not differ between the central and peripheral regions. The findings of this study represent a further source of reproducible data that should be considered when using sheep cornea as ex vivo model for experimental research. Keywords: ovine, endothelial cells, ex vivo model, vital staining, hexagonality.